High - efficiency direst somatic embryogenesis and plant regeneration from leaf base plants of "peperina" (Minthostachys verticillata) - Goytia Bertero, Valentina; Beznec, Ailin; Faccio, Paula Daniela; Auteri, Micol Tais; Arteaga, Martin; Bonafede, Marcos; Bossio, Maria Emilia (Springer, 2020)
In vitro culture has been recognized as a potential plant clonal propagation tool for a broad variety of commercial, ornamental, and medicinal species, with applications in both industrial and academic laboratories. In this study, we describe somatic embryogenesis and plant regeneration protocol for “peperina” plants (Minthostachys verticillata (Griseb.) Epling). In vitro shoots developed via shoot apex extracted from greenhouse-grown plants were cultured on shoot elongation medium (ShM) consisting of Murashige and Skoog (MS) basal salts supplemented with myoinositol, thiamine, and benzyladenine. Shoot apexes were disinfected with 70% ethanol for 5 min and 0.26 sodium hypochlorite (w/v) for 5 min, before the initiation of in vitro culture. For somatic embryo (SE) induction, leaves collected from 2-mo-old in vitro raised shoots were cultured on MS basal medium supplemented with benzyladenine and two different concentrations of coconut water (CW) until SE developed. Using 2.5% CW-supplemented medium, 100% of cultured leaves developed SE and 89.3% of the leaf explants developed plantlets. The resulting embryos germinated on the same medium, and the plantlets obtained were transferred onto ShM until they developed 3 to 4 leaves. To increase the low root development, shoots were transferred into fully hydrated perlite for rooting and then transplanted into soil-perlite containing pots for hardening. This protocol provides the first step to supply the demand and simultaneously protect the natural populations of Minthostachys verticillata from overexploitation. Furthermore, this protocol provides the first step for crop improvement by genetic modification (editing or transgenesis).